Osteoid Osteoma of the Hamate Presenting As a Midcarpal Synovitis - Salva-Coll, Guillem; Terrades-Cladera, Xavier (Journal of Wrist Surgery, 2015)
Background Osteoid osteoma is a benign bone lesion of unknown etiology uncommonly affecting the carpal bones. In the upper extremity, the clinical and imaging picture may be misleading, often mimicking other entities. We present a rare case of a patient with a subchondral osteoid osteoma mimicking a posttraumatic midcarpal synovitis.Case Description A 21-year-old woman presented with persistent pain and swelling of the right wrist. Physical examination revealed swelling and pain on direct palpation over the dorsal aspect of the wrist. Radiographs were normal. Inconclusive computed tomography (CT) and magnetic resonance imaging (MRI) scans suggesting an occult fracture versus avascular necrosis delayed the diagnosis. Scintigraphy and fine-cut CT scan provided the definitive diagnosis. Surgical excision of the nidus and synovectomy of the midcarpal joint were performed, with complete resolution of pain and rapid return to normal function.Literature Review Three different types of osteoid osteoma have been described according to radiological methods: cortical, medullar, and subperiosteal. When localized in the carpus, most lesions are intra-articular. Reactive synovitis is often present and may be the primary symptom. Radiofrequency ablation is a treatment alternative. However, if a safe distance between the electrode and a major neurovascular structures (up to 1.5 cm) cannot be guaranteed, surgical excision is recommended.Clinical Relevance A high index of suspicion and careful attention to the clinical picture are necessary for accurate diagnosis and treatment of osteoid osteoma in the hand and carpus. CT scan and scintigraphy are the most sensitive complementary investigations and enable definitive diagnosis and treatment.
Keywords: osteoid osteoma; hamate; carpal neoplasms